Mensurações do bulbo ocular e cálculo do poder dióptrico da lente intraocular em miniporcos brasileiros - Barros, Rodrigo [UNESP] (2015)
The aim of this study is to determine the refractive power of intraocular lens (IOL) of Brazilian minipigs and the dimensions of the eyeball. Total of 17 animals (34 eyes) healthy, adult, males and females, with average weight of 70kg were used. For every eye, A-mode ultrasound, keratometry and the measure of limbo-to-limbo distance were conducted; all of them variables for calculating the refractive power of the IOL. That value was obtained using different formulas and Holladay IOL Consultant® Software. Were additionally compared the ocular measurements for sex, laterality of the eye and the different formulas used in this study (Haigis, Hoffer Q, SRK / T, Holladay I and Holladay II). In the comparison between sex and laterality of the eye, there is no difference in biometric variables and power of the IOL. The application of the employed formulas (Haigis, Holladay II, Hollada I, SRK / T and Hoffer Q) allows the IOL power calculation of this specie, and the observed value ranged between 39,58±2,15 and 46,60±2,81 diopters. The minipig has an important and growing role as an experimental model for the study and practice of ophthalmic procedure, specially related to their smaller size and easily management in long term experiments